2021
DOI: 10.34117/bjdv7n9-538
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do desempenho dos centros de especialidades odontológicas (CEO) no estado do Rio Grande do Norte (RN) / Performance evaluation of dental specialty centers (CEO) in the state of Rio Grande do Norte (RN)

Abstract: ampliação e qualificação da oferta de serviços odontológicos especializados, vem implantando, desde 2004, os Centros de Especialidades Odontológicas -CEO, cujo o tratamento oferecido é uma continuidade do trabalho realizado pela rede de atenção básica. Diante dos indicadores e dados de saúde bucal desfavoráveis no país, com alto índice de edentulismo, de cárie dentária e baixa oferta de serviços reabilitadores, principalmente na Região Nordeste do Brasil, faz-se necessário a realização de uma maior e mais abra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…It was observed that type III BDSCs showed superior performance in terms of the number of specialized procedures and were able to achieve the established goals in the eld of periodontology. These results are in line with the research conducted by Da Silva and colleagues in 2021 23 , where it was observed that services with more dental chairs and a more skilled team recorded a higher volume of appointments.…”
Section: Discussionsupporting
confidence: 92%
“…It was observed that type III BDSCs showed superior performance in terms of the number of specialized procedures and were able to achieve the established goals in the eld of periodontology. These results are in line with the research conducted by Da Silva and colleagues in 2021 23 , where it was observed that services with more dental chairs and a more skilled team recorded a higher volume of appointments.…”
Section: Discussionsupporting
confidence: 92%
“…Quando há os processos de autoavaliação nos CEO, também haverá o monitoramento e a análise de metas, o que aponta uma evidente direção do quanto essa ferramenta está associada aos objetivos da produção, concordando com a análise do presente artigo (MAGALHÃES et al, 2015;DE LUCENA et al, 2019). ANTUNES, 2020;DA SILVA et al, 2021;LOPES et al, 2020).…”
Section: Discussionunclassified
“…They work in line with Primary Health Care, ensuring the interface with the health system according to the city’s epidemiological reality [ 1 ] and patient needs. The main problems in the functioning of patient regulation in CEOs are the absence of protocols that guide professionals on when and how to refer the patient, the high rate of absenteeism and evasion, and the large number of people who seek dental care directly in CEOs, without going to the PHC before [ 2 – 5 ].…”
Section: Introductionmentioning
confidence: 99%